The Coexistence of Large and Small Firms: A Study of the Italian Mechanical Industries - Wellisz, Stanislaw H. (Quarterly Journal of Economics, 1957)
Introduction, 116. — I. The structure of the Italian mechanical industries, 117. — II. The market for consumers' durables, 118. — III. Subcontracting and peak demand orders, 122. — IV. Growth possibility of large and small firms, 124. — V. The availability of financing, 127. — VI. The vulnerability of small firms, 129. — VII. Small firms: an evil or a blessing? 130.